SISTEM PENDUKUNG KEPUTUSAN MENENTUKAN KREDIT MENGGUNAKAN METODE ANALITYCAL HIERARCY PROCESS - Indrayani, Lilis; Lubis, Zulkarnain (Fakultas Teknik, Universitas Tadulako, 2021)
The research is aimed at designing a decision-making system for the determination of credit using the Analytical Hierarchy Process (AHP). Determining the provision of credit is still done manually so it takes a long time for data processing, as well as the assessment made by the leadership in determining the feasibility of the loan is still subjective. The research design used is a structured Unified Modeling Language (UML) that consists of the design of model use case diagrams, activity diagrams, sequence diagrams, and class diagrams, while programming languages use PHP, JavaScript, and MySql for database processing. The method used in obtaining results is Analytical Hierarchy Process (AHP). The result of the design of the decision-making system for the determination of credit using the Analytical Hierarchy Process (AHP), among others, provides the calculation of the expansion of credit and can provide a credit feasibility report for the customer who has filed.